2011
DOI: 10.1177/0091270010366146
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling of Pantoprazole in Pediatric Patients From Birth to 16 Years

Abstract: The population pharmacokinetics of pantoprazole was characterized in pediatric patients from birth to 16 years using NONMEM and evaluated via bootstrap and predictive check. Data were described using a 2-compartment model with a typical parameterized in terms of clearance (CL) (95% CI) of 1.93 L per hour (1.53, 2.61), given the reference covariates (female, full term, extensive/unknown CYP2C19 metabolizer status, non-African American, 10 kg weight, intravenous or tablet administration). Pantoprazole pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
3
24
1
2
Order By: Relevance
“…Figure 3 illustrates the apparent oral clearance (CL/F) of pantoprazole in patients from the neonatal period through adolescence [35]. These data were derived from a series of clinical trials submitted to the US FDA for approval and depict information from subjects whose CYP2C19 genotype would predict an extensive metabolizer phenotype.…”
Section: Pharmacokinetics and The Disposition Of Ppis In Infants And mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 illustrates the apparent oral clearance (CL/F) of pantoprazole in patients from the neonatal period through adolescence [35]. These data were derived from a series of clinical trials submitted to the US FDA for approval and depict information from subjects whose CYP2C19 genotype would predict an extensive metabolizer phenotype.…”
Section: Pharmacokinetics and The Disposition Of Ppis In Infants And mentioning
confidence: 99%
“…Dashed lines represent apparent ‘best fit’ from non-linear (for subjects from birth through 0.5 years of age) and linear (for subjects from 0.5 to 16 years of age) regressions of the data and are provided to illustrate association between CL/F and age. Data were obtained from a series of labeling studies conducted by the study sponsor and subjected to a population-based pharmacokinetic analysis to explore age-associated effects on disposition [35]
Fig. 4 a Association between cytochrome P450 (CYP) 2C19 protein expression in the human fetus and neonate, shown by dark circles .
…”
Section: Pharmacokinetics and The Disposition Of Ppis In Infants And mentioning
confidence: 99%
“…Recent studies in children have also demonstrated the importance of CYP2C19 variants [60][61][62]. The clearance of pantoprazole was estimated in pediatric patients from birth to 16 years and was 60% lower in PMs compared to EMs [63]. Our group compared drug levels following a single dose of conventionally dosed lansoprazole with CYP2C19 genotype/metabolizer phenotype in 56 children with GERD and found a direct relationship between CYP2C19 diplotype and lansoprazole concentration [64].…”
Section: Discussionmentioning
confidence: 75%
“…In children aged 6-16 years with GERD, currently available pantoprazole delayed-release tablets can be used to provide systemic exposure similar to that in adults [142]. Simulations indicated that the 1.2-mg/kg dose provides the best comparison to adults [143]. Pantoprazole is generally well tolerated in infants and children aged 1 month through < 6 years; compared with adults receiving pantoprazole 40 mg, exposure obtained with the 1.2-mg/kg dose was similar [144].…”
Section: H²-receptor Antagonists and Proton Pump Inhibitorsmentioning
confidence: 99%